Lifestyle Medicine: A Promising tool to Restoring Health - Hameed, Ekhlas Khalid; Al-Ameri, Laith Thamer (AL-Kindy College Medical Journal, 2022)
Lifestyle Medicine is the application of evidence-based lifestyle approaches for the prevention, treatment, and even the reversal of lifestyle-related chronic diseases such as diabetes, hypertension, heart disease, obesity, polycystic ovarian diseases, dementia, arthritis, and cancers